Wheat arabinoxylans: structure, extraction and characteristics - Kaprelyants, Leonyd; Pozhitkova, Liliia; Velichko, Tatiana; Bilyk, Olena (My University, 2019)
Wheat bran is a by-product of conventional milling and is commercially available in large quantities. Beside its high content of dietary fibre it contains proteins, minerals as well as vitamins and others biologically active components. In recent years, there have been designed different approaches to incorporation of wheat bran in food products to optimize composition or physiological effects. Industrial wheat bran is one of the most representative available hemicellulosic rich products. Arabinoxylans are the predominant non-starch polysaccharides found in the structural matrix of cell walls in wheat grains, being present in large quantities in wheat bran, accounting for up to 15-20% of its composition. Their physicochemical properties define their functionality which can be beneficial in cereal-based products such as bread, where their addition could enhance the gluten matrix responsible for the aerated structure and quality of bread. A potential source of аrabinoxylans is its extraction from the wheat bran based low value as an end product of the milling process. The benefits of extraction are twofold, to enhance nutritional value wheat by-product reducing fibre content and produce a high value product for use as a functional ingredient in the bread making industry and in others foods. Extraction of arabinoxylans involves many possibilities for obtaining substances with different physicochemical properties, giving opportunity for integration in functional foods. Functional behaviour includes viscosity, water solubility, water holding capacity, oxidative cross linking and gel formation and foam stability, which are all reported to be affected by the physicochemical properties of arabinoxylans, as well as chain to chain interactions with other polymers and with the solvent. Currently no commercial supply of arabinoxylans is available in sufficient quantities to conduct functionality trials; therefore the objective of the current work was to study the feasibility of extracting arabinoxylans from the bran for future developing and scaled-up extraction process based on the analyzed methods and approaches
Keywords: wheat bran; arabinoxylans; polysaccharides; extraction; кафедра технології хлібопекарських і кондитерських виробів; пшеничні висівки; арабіноксилани; полісахариди; екстракція